2011
DOI: 10.2147/prbm.s27228
|View full text |Cite
|
Sign up to set email alerts
|

Narrated lived experiences of self-care and health among rural-living older persons with a strong sense of coherence

Abstract: Sense of coherence (SOC), with its components comprehensibility, manageability, and meaningfulness, is a major factor in the ability to cope successfully with stressors and is closely related to health. Qualitative studies related to SOC are scarce, and in this phenomenological interview study, self-care is investigated in relation to SOC. The aim of this study was to describe the lived experiences of self-care and features that may influence health and self-care among older home-dwelling individuals living in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 33 publications
(47 reference statements)
3
37
0
Order By: Relevance
“…The same observation was made in a previous study,10 and being physically and socially active in older age is, in general, an important factor for good health and well-being 47…”
Section: Discussionsupporting
confidence: 81%
“…The same observation was made in a previous study,10 and being physically and socially active in older age is, in general, an important factor for good health and well-being 47…”
Section: Discussionsupporting
confidence: 81%
“…At the same time, they valued such activities for their health and well-being, and being active, both socially and physically, could stimulate the appetite. A consciousness of the benefit of activities for maintaining health and well-being in later life has also been reported in other studies 31,38. Along with health problems and limited mobility, external factors, like slippery roads, could also influence the performance of such activities negatively.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, another study among older, home-dwelling persons31 similarly showed that being engaged with other people was a source of well-being. Orem2 argued that when “bringing in the person,” there may be several basic conditional factors that interact with the informants’ self-care, health, and well-being.…”
Section: Discussionmentioning
confidence: 94%
“…They actualized their self-care ability in a meaningful way that was important for their perception of their life situation and identity. Findings from other studies8,30,31 about self-care in older people point at their ability to act combined with a wish to go on further in life.…”
Section: Discussionmentioning
confidence: 91%